Forum van de grafiek; forumprijs '73, gewezen St. Pietersabdij 29 november - 6 januari 1974. (Mariakerke : L. Vanmelle, 1973)
Albers, Josef ; Alechinsky, Pierre ; Anderle, Jiri ; Arakawa, Shusaku ; Artschwager, Richard ; De Backer, Denijs ; Baekelmans, Guy ; Baeyens, Martin R. ; Belgeonne, Gabriel ; Bertrand, Gaston ; Bigot, Gary ; Bilquin, Jean ; Bogart, Bram ; de Bolle, Francis ; Broeck, Tejo Van Den ; Brunovsky, Albin ; Bury, Pol ; Caille, Pierre ; Callens, Dirk ; Callens, Mario ; Celie, Pieter ; Celis, Marcel ; César ; Christo ; Claessens, René ; Clarke, John Clem ; de Clercq, Hugo ; De Cock, Gilbert ; Colson, Frank ; Cottingham, Robert ; Coulon, Jean ; Daniels, Albert ; Decock, José-Anne ; Delahaut, Jo ; Delvaux, Paul ; Dewinter, Jan ; Dine, Jim ; Dix, John ; Dock, Marianne ; Driesen, Dirk ; Dubit, Philippe ; Eecken, Miki Van Der ; Van Eeckhout, Willy ; Van Eepoel, Diane ; Van Eepoel, Henri ; Etienne, Jacques ; Van den Eynde, Caroline ; Fahlström, Öyvind ; Frimout, Cyr ; Gaul, Winfred ; Gazovic, Vladimir ; Geerts, Rita ; Goezu, André ; Goode, Joe ; Graham, Dan ; Graves, Nancy ; de Guide, Frédéric ; Hapers, Denise ; Haudenhuyse, Guido ; Van Hauwe, Roland ; Hoenraet, Luc ; Van Hoeydonck, Paul ; Hofkunst, Alfred ; Van Hoof, Jozef ; Hoorne, Emiel ; Hutchinson, Peter ; Ivens, René ; Jacobs, Jos ; Jans, Jos ; Johns, Jasper ; Katz, Alex ; Keil, Helène ; De Keukelaere, Marnix ; De Keyser, Raoul ; Kimura, Kosuke ; De Kramer, Enk ; Kuyle, Ghislain ; Lagasse, Toon ; Landuyt, Octave ; Lang, Daniel ; De Lannoy, René ; Leblanc, Walter ; Leckwijck, Walter ; LeWitt, Sol ; Lichtenstein, Roy ; Lucassen ; Madlener, Jörg ; Mahieu, Jean-Marie ; Malfeyt, Andrée ; Mara, Pol ; Marchoul, Gustave ; Massart, Cecile ; Mewis, Magda ; Mineur, Michel ; Morley, Malcolm ; Moses, Ed ; Mulkers, Urbain ; Nauman, Bruce ; Van Nazareth, Herman ; Neiman, Yehuda ; Nesbitt, Lowell ; Nice, Don ; Nikos ; etc.
boek